DETERMINATION OF DISSOLVED GAS CONTENT IN PETROLEUM PRODUCTS - Єфіменко, В. В.; Іванов, С. В.; Новікова, В. Ф.; Полякова, О. В. (Proceedings of National Aviation University (archive), 2021)
The issues of air solubility in reactive urges, its influence on the fuel system operation, calculation and experimental methods for determination of oxygen and nitrogen in fuels, factors influencing the solubility process are considered. A method of chromatographic determination of the content of dissolved gases has been developed. The scheme for introduction of samples to a chromatographic column is resulted.